Pengembangan Jalamba sebagai Ornamen Arsitektural pada Rumah - Abdi Gunawan Djafar; Ernawati (Universitas Negeri Gorontalo, 2020)
Jalamba is a traditional fence from Gorontalo whose existence shows to people who sees it that there will be a celebration, going on, and has been held in that place. Apart from the customary activities, jalamba also can be found in front of the house on stilts and on the other place like the mosque. The use of jalamba of the house on stilts and the mosque shows that jalamba is not attached to the customary activities and can be used as the architectural elements that can show the cultural richness of Gorontalo. This research will discuss the development of the jambala with a focus on residential building types or a house in the first step that could be piloted to develop in other types of other buildings. This research is qualitative, data obtained trough studies, literature, and field observations. The literature being reviewed is in the form of books, internet articles, and research journals. Research result shows that the development of jalamba as the architectural elements to the house is based on the effort for developing part of the Gorontalo culture to be preserved and become part of the modern house contemporary architecture.